FRI0056 Tnfalpha therapy initiation audit: rationing on an equitable basis – the norfolk and norwich (n/n) experience. (1st June 2001) - Somerville, MF; Price-Forbes, A; Brooksby, A; Leeder, J; Gaffney, JK; Merry, P; Scott, DG
Abstract : Background: BSR 1 and EULAR 2 consensus guidelines have been published regarding the evolving use of TNF@ therapy in rheumatoid arthritis (RA). It is anticipated that demand will exceed supply. Norfolk Health Authority has allocated £210, 000 (for approximately 30 patients) for initiation of this treatment during 2000–01. An initial review highlighted discrepancies between the DAS28 (ie consensus guidelines), and our individual clinical assessment of patients. Objectives: To evaluate prospectively a cohort of consecutive eligible patients, prioritise them according to a weighted scoring system, which we developed and observe changes in the profile of those fulfilling these revised criteria for treatment. Methods: In a 3 month period, potential patients were recruited to an assessment clinic. Those fulfilling the criteria were further stratified using a 5- point cumulative scoring system based on 4 variables: 1) DAS28, 2) Age, 3) Disease duration and 4) Steroid dose. This weighted towards younger patients with shorter disease duration, requiring steroids and having a high DAS28, on the assumption that treating such patients would be more cost-effective. This resulted on a final list of 30 patients selected for treatment (N/N Priority). Results: 135 out of 139 patients assessed, fulfilled the BSR eligibility criteria. Nearly two thirds of the 30 patients with the highest DAS28 (BSR priority) were subsequently replaced on our stratified list (N/N Priority). However, funding is still not available for 78% of our patients, who are otherwise eligible for treatment. Conclusion: Rationing creates difficult choices. We have attempted to select patients according to need and cost effectiveness. These decisions should be debated openly as they have important implications for health policy and clinical management. References: British Society for Rheumatology – Report of a Working Party, April 2000 Updated consensus statement on TNF blocking drugs for the treatment of RA. Ann Rheum Dis . 2000;59 (Suppl I):i1–i2